2017
DOI: 10.1038/bmt.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting conditioning dose in newly diagnosed light chain amyloidosis undergoing frontline autologous stem cell transplant: impact on response and survival

Abstract: Autologous stem cell transplantation (ASCT) is an important treatment modality in light chain (AL) amyloidosis. Use of reduced-dose melphalan conditioning is common, given the associated organ and functional decline. The impact of full-intensity melphalan conditioning (n=314) was compared to reduced-dose conditioning (n=143). Patients in the full-intensity group were younger, with better performance status, fewer involved organs, lower tumor burden and lower Mayo stage. Full-dose conditioning was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…Lower doses of melphalan could reduce treatment related toxicity, but also lower hematologic responses. 94 The largest experience with HDM/SCT for AL amyloidosis is from the Mayo Clinic and Boston University. In 421 patients treated with HDM/SCT at Boston University, TRM was 11% overall, and decreased to 6% in the last 5 years of the study 95 .…”
Section: [H2] Patient Risk Stratificationmentioning
confidence: 99%
“…Lower doses of melphalan could reduce treatment related toxicity, but also lower hematologic responses. 94 The largest experience with HDM/SCT for AL amyloidosis is from the Mayo Clinic and Boston University. In 421 patients treated with HDM/SCT at Boston University, TRM was 11% overall, and decreased to 6% in the last 5 years of the study 95 .…”
Section: [H2] Patient Risk Stratificationmentioning
confidence: 99%
“…Conditioning dose has previously been reported as a significant predictor of survival with those receiving reduced intensity conditioning having worse outcomes. 26,27 In our data, full intensity conditioning with melphalan 200 mg/m 2 was associated with a significantly longer OS only in the l cohort (l: median OS 146 months for melphalan 200 mg/m 2 vs 45 months for melphalan ,200 mg/m 2 , P , .0001 and k: median OS not reached for both groups, P 5 .33). We noted a significant difference in 100-day all-cause mortality in the l group depending on conditioning dose (3.8% for melphalan 200 mg/m 2 vs 13.9% for melphalan ,200 mg/m 2 , P 5 .0006).…”
Section: Resultsmentioning
confidence: 55%
“…Median overall survival (OS) was 10.5 years for those receiving full-intensity HDM compared with 5.2 years for patients receiving mHDM (P < .0001). A Center for International Blood and Marrow Transplant Research study also showed a reduced risk of hematologic relapse with higher doses of melphalan [5], as did a report from the Mayo Clinic [6].…”
Section: Introductionmentioning
confidence: 76%
“…HDM/SCT have been the cornerstone of treatment for AL amyloidosis for more than 2 decades, with durable responses, prolonged survival, and decreasing TRM [3,4,8,17]. However, for patients who do not qualify for the full conditioning dose of melphalan because of poor functional status and/or advanced amyloid-related organ dysfunction, the question of whether to treat with mHDM with SCT versus a novel therapeutic agent is still unanswered [6][7][8]. Patients who receive mHDM/SCT have historically had poorer outcomes than those who received the full dose of melphalan with SCT with respect to hematologic response and survival, but it is still unknown whether this difference is solely attributable to differences in baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%